Implementation and Evaluation of a Smartphone Application for the Perioperative Care of Neurosurgery Patients at an Academic Medical Center: Implications for Patient Satisfaction, Surgery Cancelations, and Readmissions. Issue 3 (25th May 2017) - Felbaum, Daniel R; Stewart, Jeffrey J; Anaizi, Amjad N; Sandhu, Faheem A; Nair, Mani N; Voyadzis, Jean-Marc
Abstract: BACKGROUND: Smartphone applications (apps) in the health care arena are being increasingly developed with the aim of benefiting both patients and their physicians. The delivery of adequate instructions both before and after a procedure or surgery is of paramount importance in ensuring the best possible outcome for patients. OBJECTIVE: To demonstrate that app-based instructions with built-in reminders may improve patient understanding and compliance and contribute to reducing the number of surgery cancellations and postoperative complications and readmissions. METHODS: We prospectively accrued 56 patients undergoing routine neurosurgery procedures who subsequently downloaded the app. The median age was 54 (range 27-79). Patients were followed for successful registration and use of the app, compliance with reading instructions before and after surgery, and sending pain scores and/or wound images. The number of surgeries cancelled, postoperative complications, 30-d readmissions, and phone calls for surgery-related questions were examined. RESULTS: Fifty-four of the 56 patients successfully registered, downloaded, and used the app and read and complied with instructions both before and after surgery. There were no cancelled surgeries. There was 1 postoperative complication. There were no readmissions. Eight of the 54 patients (14.8%) called the office on a single occasion for a surgery related question. CONCLUSION: We demonstrate the utility of a smartphone application in the perioperative neurosurgical care setting with regard to patient compliance and satisfaction as well as surgery cancellations and readmissions. Further study of a larger number of patients with a control group is warranted.